Spectroscopic and Kinetic Investigation of the Fully Reduced and Mixed Valence States of Ba 3-Cytochrome C Oxidase From Hermus Thermophilus a Fourier Transform Infrared (FTIR) and Time-Resolved Step-Scan FTIR Study - Koutsoupakis, Constantinos; Soulimane, Tewfik; Varotsis, Constantinos (My University, 2012)
Background: Cytochrome c oxidase reduces O 2 to H 2O, a reaction coupled to proton translocation across the membrane. Results: Photolysis of CO from the mixed valence form of cytochrome ba 3-CO does not lead to a heme a 3 3+-Cu B 1+-CO binuclear center. Conclusion: The absence of reverse electron transfer between hemes a 3 and b is shown. Significance: Unique thermodynamic and kinetic properties of cytochrome ba 3 oxidase are presented
Keywords: Porphyrins; Photochemistry; Cytochrome oxidase; Carbon monoxide; Infrared spectroscopy; Thermodynamics